Impact of the COVID-19 Pandemic on Global Diseases and Human Well-Being - Lo Giudice, Arturo; Asmundo, Maria Giovanna; Cimino, Sebastiano; Russo, Giorgio Ivan (Journal of clinical medicine, 2022)
This editorial of the Special Issue “Impact of SARS-CoV-2 Pandemic on Global Diseases and Human Well-Being” aims to portray the repercussions of the novel COVID-19 emergency on a wide range of health issues [...]